The Impact of Social Media Marketing on Brand Awareness, Engagement, and Purchase Intention - Setiawan, Budi; Fadre, Lady Angelina (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2025)
In the digital era, social media marketing has become an essential strategy for fashion brands to build consumer relationships and influence purchasing decisions. However, in Indonesia, Uniqlo’s social media efforts have shown mixed results, with some consumers lacking awareness and engagement despite the brand’s active online presence. This study aims to examine how social media marketing influences brand awareness, consumer brand engagement, and purchase intention among Uniqlo consumers in Indonesia. A quantitative approach was employed, targeting individuals who have purchased Uniqlo products and interacted with the brand’s social media platforms. Data were collected through an online questionnaire and analyzed to explore the relationships among the variables. The findings indicate that social media marketing positively affects brand awareness and consumer engagement, both of which play important roles in shaping purchase intention. The results highlight that interactive and informative content strengthens brand recognition and fosters emotional connections, which in turn increase consumers’ willingness to buy. Based on these findings, it is recommended that Uniqlo and similar fashion retailers enhance their digital strategies by delivering more personalized, engaging, and consistent messaging to boost consumer response and loyalty.